Susceptibilidad antimicrobiana in vitro de cepas de Salmonella spp. en granjas de ponedoras comerciales del departamento de Antioquia (2006)
ABSTRACT: The appearance of antimicrobial-resistant Salmonella spp is associated with the use of antibiotics for therapeutic or production porpuses in animals. Antimicrobial-resistant bacteria can be transmitted to humans through contaminated food of animal origin. In this study we tested the susceptibility of Salmonella spp. isolated in pultry farms (from healthy hens, premises, equipment and feed) to some antimicrobial agents used in humans. The method used was Bauer & Kirby and Minimal Inhibitory Concentrations by microdilution method automatic system Vitek®. The results were as fallows: by the Bauer & Kirby method, one hundred percent of isolates were sensitive to Amoxicillin and Chloramphenicol and 6.7% of isolates were intermediate and 3.3% of isolates were resistant to Tetracycline. The antimicrobials agents tested by Minimal Inhibitory Concentrations were Ampicillin, Ampicillin/Sulbactam, Piperaciline/ Tazobactam, Meropenem, Imipem, Cephalothin, Amikacin, Gentamicin, Ciprofloxacin, Trimethoprim/ sulfa. One hundred percent of the isolates were sensitive to these antibiotics. Antimicrobial resistantance of Salmonella spp has been reported previously. We recommend studies to monitor bacterial susceptibility for the sake of public health.